'When you are homeless, you are not thinking about your medication, but your food, shelter or heat for the night': behavioural determinants of homeless patients' adherence to prescribed medicines. (July 2017) - Paudyal, V.; MacLure, K.; Buchanan, C.; Wilson, L.; Macleod, J.; Stewart, D.
Abstract: Objectives: This study aimed to explore behavioural determinants of homeless patients' adherence to prescribed medicines using Theoretical Domains Framework (TDF). Study design: A qualitative study using semi-structured, face-to-face interviews. Methods: Participants were recruited from a homelessness primary healthcare centre in Aberdeen, United Kingdom (UK). Face-to-face interviews were audio-recorded and transcribed verbatim. Thematic analysis of the interview data was conducted using the Framework Approach based on the Theoretical Domains Framework. National Health Service ethical and Research and Development (R&D) approval was obtained. Results: Twenty-five patients were interviewed, at which point data saturation was achieved. A total of 13 out of 14 Theoretical Domains Framework domains were identified that explained the determinants of adherence or non-adherence to prescribed medicines. These included: 'beliefs about consequences' (e.g. non-adherence leading to poor health); 'goals' of therapy (e.g. being a 'normal' person with particular reference to methadone adherence); and 'environmental context and resources' (e.g. stolen medicines and the lack of secure storage). Obtaining food and shelter was higher priority than access and adherence to prescribed medicines while being homeless. Conclusions: Behavioural determinants of non-adherence identified in this study were mostly related to participants' homelessness and associated lifestyle. Results are relevant to developing behaviour change interventions targeting non-adherent homeless patients and to the education of healthcare professionals serving this vulnerable population. Highlights: Behavioural determinants of medicines adherence by homeless patients were explored. Social influences and environmental factors were amongst key determinants. Health professionals can impact adherence through awareness of the determinants.